2023
DOI: 10.1021/acs.jpcc.3c02111
|View full text |Cite
|
Sign up to set email alerts
|

Phonons of Atomically Thin ZnSe Nanoplatelets Grown by the Colloidal Method

Abstract: In this work, the phonon spectra of atomically thin ZnSe nanoplatelets (NPLs) were studied using Raman and infrared spectroscopies. Atomically thin ZnSe NPLs were grown on the Si substrate covered with a 100 nm thick gold layer by the colloidal method in the temperature range of 100−170 °C. The triangular and rectangular NPLs with 2.5-and 4-monolayer thicknesses, respectively, were synthesized, as determined by atomic force microscopy (AFM) measurements. Longitudinal optical (LO) and transverse optical (TO) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…TEM analysis showed that this absorption profile corresponds to ZnSe NPLs (Figure S16). We determined that this population is 3 ML wurtzite ZnSe NPLs, as the observed transition energy of 3.92 eV (316 nm) and 4.06 eV (305 nm) match the calculated band energy for the heavy and light hole of 3 ML w-ZnSe, respectively. , The thickness measured from TEM images aligns with the expected thickness (Figure S17). However, due to the low image contrast, our conclusion is mainly driven by their optical properties.…”
Section: Resultsmentioning
confidence: 67%
“…TEM analysis showed that this absorption profile corresponds to ZnSe NPLs (Figure S16). We determined that this population is 3 ML wurtzite ZnSe NPLs, as the observed transition energy of 3.92 eV (316 nm) and 4.06 eV (305 nm) match the calculated band energy for the heavy and light hole of 3 ML w-ZnSe, respectively. , The thickness measured from TEM images aligns with the expected thickness (Figure S17). However, due to the low image contrast, our conclusion is mainly driven by their optical properties.…”
Section: Resultsmentioning
confidence: 67%
“…At this point, zinc chalcogenide-based semiconductors have been considered as a promising alternative with their suitable energy band gaps. , Particularly, ZnSe having a direct band gap of 2.7 eV is very attractive for blue light-emitting applications. So far, efforts have predominantly focused on spherical-shaped ZnSe-based NCs, with less exploration into other morphologies such as nanowires (NWs), nanorods (NRs), and NPLs. In addition to the bare ZnSe NCs of varying sizes, studies have also investigated alloying high band gap ZnSe with low band gap ZnTe to further engineer emission colors within the blue/green spectral range (420–500 nm) . Recently, Kim et al demonstrated that the PLQY of ZnSe-based NCs could be increased to nearly unity by surface treatment with hydrofluoric acid to eliminate trap sites and with zinc chloride to effectively passivate the surfaces .…”
Section: Introductionmentioning
confidence: 99%